Adaptation to an autoimmune disorder: Does mental flexibility impact illness-related self-regulation?. Issue 3 (3rd March 2016) - Karademas, Evangelos C.; Ktistaki, Georgia; Dimitraki, Georgia; Papastefanakis, Emmanouil; Kougkas, Nikolaos; Fanouriakis, Antonios; Gergianaki, Irini; Bertsias, George; Sidiropoulos, Prodromos; Simos, Panagiotis
Abstract : Objective : To examine whether mental flexibility moderates the relationship between illness representations of control and coping behaviour in individuals suffering from rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE). Design : Recently, diagnosed RA ( N  = 80) and SLE ( N  = 75) patients completed questionnaires about illness representations of personal and treatment control and four coping behaviours: instrumental coping, adherence to medical advice, palliative coping and wishful thinking. Mental flexibility was assessed with the Trail Making Test Part B (TMT-B), while visuomotor processing speed, as a confounder, was assessed with the Trail Making Test Part A (TMT-A). Moderated mediation models were tested within a bootstrapped multiple regression framework. Results : TMT-A scores had no statistically significant moderation effects on the relation between representations and coping behaviour. Conversely, in those participants with SLE, TMT-B scores moderated the relation of personal control to wishful thinking and palliative coping, as well as the relation of treatment control to both wishful thinking and palliative coping. All significant effects were restricted to the SLE group. Conclusion : Interactions between neurocognitive factors and the process of illness adaptation may emerge early during the course of SLE. The present findings highlight the role of cognitive functioning as an integral part of the illness-related self-regulation mechanism.